2008
DOI: 10.1086/528756
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme Diversity and Geographical Differentiation ofParasenecio adenostyloides(Asteraceae), an Endemic Forest Herb in Japan

Abstract: In this study, allozyme variation at 15 putative loci was analyzed in 11 populations of Parasenecio adenostyloides (Asteraceae), a perennial herb endemic to Shikoku and Honshu, Japan. This species occurs mainly in the understory of subalpine coniferous forests and shows an islandlike pattern of geographical distribution. Genetic variation at the species level (P ¼ 73:3, mean number of alleles per locus A ð Þ ¼ 4:00, expected heterozygosity H E ð Þ ¼ 0:237) and at the population level (percentage of polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, the genetic structure of a component of sub-alpine coniferous forests, Parasenecio adenostyloides, was not in agreement with that of A. mariesii. Nakagawa (2008) reported that this species maintained extremely limited amounts of genetic variation in southwestern Japan, suggesting that this pattern of P. adenostyloides, seems to have been primarily shaped by current geographical isolation among populations, i.e., ecological factors, rather than by historical factors.…”
Section: Review Of Plant Phylogeography In Japanmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the genetic structure of a component of sub-alpine coniferous forests, Parasenecio adenostyloides, was not in agreement with that of A. mariesii. Nakagawa (2008) reported that this species maintained extremely limited amounts of genetic variation in southwestern Japan, suggesting that this pattern of P. adenostyloides, seems to have been primarily shaped by current geographical isolation among populations, i.e., ecological factors, rather than by historical factors.…”
Section: Review Of Plant Phylogeography In Japanmentioning
confidence: 98%
“…Alpine and sub-alpine: Parasenecio adenostyloides (Nakagawa 2008), Picea jezoensis (Aizawa et al 2007(Aizawa et al , 2009, Pinus parviflora (Tani et al 2003), and Pinus pumila (Tani et al 1996) Montane: Quercus crispula Chamaecyparis obtusa (Tsumura et al 2007b;Matsumoto et al 2010), Conocephalum conicum (Akiyama and Hiraoka 1994), Cryptomeria japonica (Takahashi et al 2005), and Fagus japonica (Hiraoka and Tomaru 2009a) Lowland: Raphanus sativus var. (Huh and Ohnishi 2001;Ohsako and Ohnishi 2007).…”
Section: Typical Phylogeographical Patterns and The Effects Of Mountainsmentioning
confidence: 99%